2021
DOI: 10.3389/fmolb.2021.685174
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 Variation in Taiwanese General Population and the Cancer Cohort

Abstract: BRCA1 and BRCA2 (BRCA) play essential roles in maintaining genome stability. Rapidly evolving human BRCA generates oncogenic variants causing high cancer risk. BRCA variation is ethnic-specific in reflecting adaptation and/or effects of genetic drift. Taiwanese population of 23.8 million is an admixture of multiple ethnic origins; Taiwan’s subtropical and tropical climate and geographically islandic location provide a unique natural environment. Therefore, Taiwanese population provides a unique model to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
9
1
Order By: Relevance
“…The prevalence of BRCA PLP is between 0.2% and 0.5% in modern human population. For example, the prevalence is 0.26% in Japanese population (Momozawa et al, 2018), 0.29% in Macau population (Qin et al, 2021), 0.38% in Chinese population (Dong et al, 2021), 0.38% in Mexican population (Fernandez-Lopez et al, 2019), 0.39% in Malaysian population (Wen et al, 2018), 0.53% in Taiwanese population (Chian et al, 2021), and 0.53% in Caucasian populations Positive selection imposed on the reproductive stage can select the BRCA PLP not deleterious at the stage. However, our current study does not determine whether one or both of the explanations could contribute to the higher prevalence of BRCA PLP in modern human population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of BRCA PLP is between 0.2% and 0.5% in modern human population. For example, the prevalence is 0.26% in Japanese population (Momozawa et al, 2018), 0.29% in Macau population (Qin et al, 2021), 0.38% in Chinese population (Dong et al, 2021), 0.38% in Mexican population (Fernandez-Lopez et al, 2019), 0.39% in Malaysian population (Wen et al, 2018), 0.53% in Taiwanese population (Chian et al, 2021), and 0.53% in Caucasian populations Positive selection imposed on the reproductive stage can select the BRCA PLP not deleterious at the stage. However, our current study does not determine whether one or both of the explanations could contribute to the higher prevalence of BRCA PLP in modern human population.…”
Section: Discussionmentioning
confidence: 99%
“…The BRCA2 variant was consistently reported to be pathogenic; for the SPINK1 variant, there were conflicting interpretations of pathogenicity, with nine identifying it as pathogenic and one as uncertain significance. These two variants had both been reported as pathogenic variants in published pancreatic cancer studies ( Chian et al, 2021 ; Yin et al, 2022 ). Although the other variants in BRCA1 , ATM , and POLQ were not previously reported and were identified as novel variants in this current study, pathogenic variants in these genes have also been reported in pancreatic cancer and therefore these genes have been known to cause PDAC ( Earl et al, 2020 ; Mizukami et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Our data are consistent with other studies in the field of VUS reclassification of BRCA1/2 genes. The problem regarding VUS reclassification has been discussed mostly for Asian populations, where the frequency of VUS reaches 60% (Nakamura et al, 2016;Kwong et al, 2016;Chian et al, 2021). In the study of Sinha (2020), the authors created own model where they measured the effect of variants on the structural conformations of BRCT repeats using molecular dynamics simulation (MDS) consisting of RMSD (Root-mean-square-deviation), RMSF (Root-mean-square-fluctuations), Rg (Radius of gyration), SASA (Solvent accessible surface area), NH bond (hydrogen bond) and Covariance analysis.…”
Section: Discussionmentioning
confidence: 99%